2011
DOI: 10.1177/1947601911432495
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p21-Dependent G1/G2 Arrest in the Absence of DNA Damage as an Antiapoptotic Response to Metabolic Stress

Abstract: The folate enzyme, FDH (10-formyltetrahydrofolate dehydrogenase, ALDH1L1), a metabolic regulator of proliferation, activates p53-dependent G1 arrest and apoptosis in A549 cells. In the present study, we have demonstrated that FDH-induced apoptosis is abrogated upon siRNA knockdown of the p53 downstream target PUMA. Conversely, siRNA knockdown of p21 eliminated FDH-dependent G1 arrest and resulted in an early apoptosis onset. The acceleration of FDH-dependent apoptosis was even more profound in another cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 66 publications
(112 reference statements)
2
35
0
Order By: Relevance
“…Four reduced folate forms represent the majority of the folate pool in mammalian cells (tetrahydrofolate (THF), 5-methyltetrahy- drofolate (5-CH 3 -THF), 5,10-methylenetetrahydrofolate (5,10-CH 2 -THF), and 10-formyltetrahydrofolate (10-CHO-THF)), whereas in plasma, 5-CH 3 -THF comprises more than 90% of the reduced folate (41). We measured reduced folate pools in blood, lung, and liver using a technique allowing the measurement of major folate forms independent of their polyglutamylation status (30,31). We observed that the total folate in blood, represented mostly by 5-CH 3 -THF, was decreased 2.2-fold in mice kept on folate-free chow compared with mice on a typical folate diet (Fig.…”
Section: Dietary Folate Promotes Lung Colonization By Cancer Cells Anmentioning
confidence: 89%
See 1 more Smart Citation
“…Four reduced folate forms represent the majority of the folate pool in mammalian cells (tetrahydrofolate (THF), 5-methyltetrahy- drofolate (5-CH 3 -THF), 5,10-methylenetetrahydrofolate (5,10-CH 2 -THF), and 10-formyltetrahydrofolate (10-CHO-THF)), whereas in plasma, 5-CH 3 -THF comprises more than 90% of the reduced folate (41). We measured reduced folate pools in blood, lung, and liver using a technique allowing the measurement of major folate forms independent of their polyglutamylation status (30,31). We observed that the total folate in blood, represented mostly by 5-CH 3 -THF, was decreased 2.2-fold in mice kept on folate-free chow compared with mice on a typical folate diet (Fig.…”
Section: Dietary Folate Promotes Lung Colonization By Cancer Cells Anmentioning
confidence: 89%
“…Lysates were chilled on ice and centrifuged for 5 min at 17,000 ϫ g at 4°C. Folate pools were measured in tissue lysates by the ternary complex assay method as we described previously (30,31). Folate levels were calculated per milligram of protein measured by Bradford assay or per milliliter of whole blood.…”
Section: Methodsmentioning
confidence: 99%
“…This downregulation is achieved through extensive methylation of the ALDH1L1 promoter and apparently serves the purpose of relieving transformed cells from one of the proliferation controlling mechanisms (34). In agreement with this mechanism, reconstitution of Aldh1l1 in Aldh1l1-deficient cancer cells produces strong antiproliferative effects including cell cycle arrest (35,36), inhibition of motility (37), and apoptosis (35). The antiproliferative effect of Aldh1l1, resulting from the decrease in the intracellular purine levels (38) and impaired folate-dependent homocysteine remethylation (39), is mediated by numerous downstream effectors including p53, p21, PUMA, JNK1/2, c-Jun, caspases 3, 8, and 9, protein phosphatase 1/protein phosphatase 2A, and cofilin (36 -38, 40, 41).…”
mentioning
confidence: 86%
“…Transfections were performed following the manufacturer's protocol. Silencing of PUMA by siRNA was carried out as we described previously (36). Tet-On A549/Aldh1l1 cells (1.2 ϫ 10 5 ) were transfected with 25 nmol of Stealth RNAi (Invitrogen) using 5-10 l of Lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation